The role and function of systemic collaborative intermediary organisations in urban system change: the case of the Cities Alliance - Hosken, Adele (Department of Civil Engineering, 2019)
Misaligned, single actor and sector driven approaches result in urban system fragmentation which creates barriers to achieving the United Nations’ Sustainable Development Goals. The study argues for the alignment of the interests, resources and behaviours of actors to work together across local, national, regional and global urban system levels. This is an essential precondition for transitioning towards urban sustainability. It builds on the argument that systems change when developments at all levels link up and reinforce each other. The study contributes to the literature on the role of cross-sector collaboration and collaborative governance in urban sustainability transitions in three ways by: (1) extending the understanding on how intermediary functions are applied to scale urban collaborative governance; (2) developing the concept of a SCIO and a conceptual model for urban system change and describing the role of SCIOs to operationalise the conceptual model; and (3) contributing to the emerging understanding of how to make an abstract global agenda on collaboration, SDG Goal 17, more concrete by discussing the case of a global urban intermediary and multi-stakeholder partnership. It distinguishes between universal and systemic intermediary functions and discuss how these are applied across horizontal and vertical scales to foster collaborative governance and alignment. This contributes towards the understanding of how multi-level urban governance is organised and highlights the challenges and limitations encountered in scaling urban collaborative governance.